Long noncoding RNA MACC1-AS1 promotes the stemness of hepatocellular carcinoma cells by antagonizing miR-145. Issue 4 (April 2020) - Guo, Yuling; Zhong, Jiuhong; Wu, Fang; Zhan, Zhengyu
Objectives: This work aimed to investigate the roles of long noncoding (lnc)RNA MACC1-AS1 (MACC1 antisense RNA 1) in progression of hepatocellular carcinoma (HCC). Methods: Real-time quantitative PCR, western blot, spheroid formation, aldehyde dehydrogenase isoform 1 (ALDH1) activity analysis, luciferase reporter assay, and RNA pull-down analysis were used to examine MACC1-AS1–mediated effects on HCC cell stemness. Results: MACC1-AS1 was highly expressed in HCC tissues and cells. MACC1-AS1 positively regulated the expression of stemness master regulators and inhibited spheroid-forming ability and ALDH1 activity. Furthermore, MACC1-AS1 promoted the stemness of HCC cells by antagonizing microRNA (miR)-145 activity. Overexpression of miR-145 also attenuated HCC cell stemness. Conclusions: This work revealed a novel MACC1-AS1/miR-145 axis that regulates the stemness of HCC cells.